2020
DOI: 10.4274/balkanmedj.galenos.2020.2019.8.25
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pre-transplant Cell-free DNA Levels on Leukemia Relapse and Transplant-related Complications in Allogeneic Hematopoietic Stem Cell Transplant Recipients

Abstract: Background: Cell-free DNA, which may be considered as "liquid" biopsy, may serve as a diagnostic and prognostic marker not only in hematological malignancies but in solid tumors as well. Aims: To investigate the prognostic role of pre-transplant cell-free DNA levels in allogeneic hematopoietic stem cell transplant recipients. Study Design: Retrospective cohort study. Methods: A total of 177 allogeneic hematopoietic stem cell transplant recipients [median age: 36 (16-66) years; male/female: 111/66] with an init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Hematopoietic stem cell transplantation can cure childhood leukemia, aplastic anemia, hemoglobin disease, and congenital immune deficiency [ 28 ]. The pretreatment regiments for pediatric transplantation include total body irradiation (TBI) and chemotherapy alone [ 29 32 ]. The most classical pretreatment regiments are TBI/CY and BU/CY.…”
Section: Discussionmentioning
confidence: 99%
“…Hematopoietic stem cell transplantation can cure childhood leukemia, aplastic anemia, hemoglobin disease, and congenital immune deficiency [ 28 ]. The pretreatment regiments for pediatric transplantation include total body irradiation (TBI) and chemotherapy alone [ 29 32 ]. The most classical pretreatment regiments are TBI/CY and BU/CY.…”
Section: Discussionmentioning
confidence: 99%
“…Another study on pediatric ALL looked into the level of clonal Ig/TCR gene rearrangements in plasma and compared it to MRD determined by flow cytometry in BM. The authors came to the conclusion that both approaches could independently predict relapse despite the methods’ poor correlation ( 49 ). All these studies have shown that MRD monitoring of the PB appears to be an adequate alternative to frequent BM aspirations, however, additional studies investigating the biology of liquid biopsies in ALL and its potential as an MRD marker in larger patient cohorts within current treatment protocols are warranted.…”
Section: Mrd Assessment Using Liquid Biopsy In Different Malignanciesmentioning
confidence: 99%
“…They did not show a correlation, but the peripheral blood could predict a relapse [ 87 ]. Another study showed that BCR/ABL1 -positive ALL patients had lower pre-transplant cfDNA levels than BCR/ABL1 -negative ALL patients [ 88 ]. More studies are needed to use cfDNA for monitoring the MRD in ALL.…”
Section: Lymphoid Malignanciesmentioning
confidence: 99%